The FAcilitates Chromatin Transcription complex regulates the ratio of glycolysis to oxidative phosphorylation in neural stem cells. - Lou, Y.; Wu, L.; Cai, W.; Deng, H.; Sang, R.; Xie, S.; Xu, X.; Yuan, X.; Wu, C.; Xu, M.; Ge, W.; Xi, Y.; et al. (Journal of molecular cell biology, 2024)
Defects in the FAcilitates Chromatin Transcription (FACT) complex, a histone chaperone composed of SSRP1 and SUPT16H, are implicated in intellectual disability. Here, we reveal that the FACT complex promotes glycolysis and sustains the correct cell fate of neural stem cells/neuroblasts in the Drosophila 3rd instar larval central brain. We show that the FACT complex binds to the promoter region of the estrogen-related receptor (ERR) gene and positively regulates ERR expression. ERR is known to act as an aerobic glycolytic switch by upregulating the enzymes required for glycolysis. Dysfunction of the FACT complex leads to the downregulation of ERR transcription, resulting in a decreased ratio of glycolysis to oxidative phosphorylation (G/O) in neuroblasts. Consequently, neuroblasts exhibit smaller cell sizes, lower proliferation potential, and altered cell fates. Overexpression of ERR or suppression of mitochondrial oxidative phosphorylation in neuroblasts increases the relative G/O ratio and rescues defective phenotypes caused by dysfunction of the FACT complex. Thus, the G/O ratio, mediated by the FACT complex, plays a crucial role in neuroblast cell fate maintenance. Our study may shed light on the mechanism by which mutations in the FACT complex lead to intellectual disability in humans.